The Impact of Science Field Courses in the Bahamas on the Personal and Professional Development of U.S. College Students, 1977-2014 - Ford, Dawn M.; Eshbaugh, W. Hardy; Branson, R. Christopher (International Journal of Bahamian Studies, 2017)
Fieldwork is a component of many college science courses. Faculty at Miami University in Oxford, Ohio and the University of Tennessee at Chattanooga have facilitated fieldwork-intensive science courses in The Bahamas for many years. The study surveyed students who participated in fieldwork in The Bahamas between 1977 and 2014, measuring the perceived impact the courses had on their personal and professional development, as well as their international perspective. Survey participants agreed the experience had a high impact on their personal development (97), professional development (91%), and international perspective (89%). General Linear Model results indicated no statistically significant differences between or within groups, suggesting participants' perceived impacts are the same regardless of gender, age, institution or field station location. Qualitative data analysis revealed several types of impact, such as understanding of and appreciation for Bahamian culture, appreciation or tropical environments, development of research skills, and enhanced career opportunities. International fieldwork in The Bahamas clearly has positive long-term impacts on students and should be continued.